Gene therapy in solid tumors: trends in trials in China and beyond. Issue 2 (February 2021) - Chen, Kun; Wang, Shuhang; Chen, Bin; Sun, Fa; Li, Ning
Highlights: Gene therapy can be classified as in vivo or ex vivo . Gene therapy has developed rapidly from World to China Mainland. In vivo approach is easier to get launched as IND. The most promising gene therapy for solid tumors in vivo is oncolytic virus. Abstract : Gene therapy involves the introduction of new genes into cells, to modify or manipulate the expression of a gene or to alter the biological properties, for the purpose of treating disease. It is designed to treat genetic diseases at their root, by correcting the mutation responsible, its success in treatment of blood cancers and rare diseases is encouraging, and it is also beginning to show promising effects against solid tumors. Here, we comprehensively analyze all the active clinical trials of gene therapy for solid tumors from January 2010 to April 2020. Our analysis highlights the increasing trends in gene therapy trials in China and elsewhere, as well as the potential of oncolytic viruses as gene therapy products for solid tumors in vivo .